Distribution of metastases in mesorectum is unpredictable: Metastases do not respect tumor localization even in small non-circumferential rectal cancers - Linter Kapišinská, Magdaléna; Hovorková, Eva; Závalová, Veronika; Šubrt, Zdeněk; Kuneš, Martin; Ferko, Alexander (European journal of surgical oncology, 2018)
INTRODUCTION: Low anterior resection with total mesorectal excision (TME) is the gold standard for surgical treatment of rectal carcinoma. The radicality of this procedure is negatively counterbalanced by morbidity, lethality, and numerous other complications. Local excision would appear to be an attractive alternative, but its radicality is disputable due to risk of undetected metastasis to the mesorectum. The study aimed to determine the location of mesorectal metastases with respect to circumferentially - located tumors in patients with tumors involving less than one-third of the rectal circumference. MATERIALS AND METHODS: Resected specimens from patients with tumors smaller than one-third of the circumference were divided into: Sector A - tumorous, and Sector B - nontumorous. Group A was created by the pathologist cutting part of the rectal wall with the adjacent mesorectum, as though imitating a full-thickness excision. RESULTS: The study comprised 35 patients with a mean age of 66 years, of which 23 were men (65.7%) and 12 were women (34.2%). Tumors were predominantly (y)pT1-T2; a total of 799 lymph nodes and 5 tumor satellites were examined. Six patients (17.1%) were identified as stage (y)pN+. A total of 3 positive findings (lymph node metastasis or satellites) were detected in 3 patients (8.5%) in tumorous Sector A; and 8 positive findings were detected in 4 patients (11.4%) in non-tumorous Sector B. CONCLUSION: Rectal carcinoma involving one-third of the rectal circumference metastasizes discontinuously, and spreads into parts of the mesorectum beyond the tumor area.
Keywords: kolonoskopie; Magnetic Resonance Imaging; intervenční ultrasonografie; magnetická rezonanční tomografie; Humans; laparoskopie; lidé středního věku; kolektomie; Female; Aged; Rectum; dospělí; mezokolon; morbidita; Rectal cancer; senioři; lidé; nádory rekta; Ultrasonography, Interventional; Mesocolon; Adult; Colectomy; Colonoscopy; staging nádorů; Follow-Up Studies; ženské pohlaví; Rectal Neoplasms; Male; Middle Aged; Morbidity; Mesorectal metastasis; Czech Republic; Aged, 80 and over; Laparoscopy; senioři nad 80 let; Total mesorectal excision; Neoplasm Staging; Česká republika; mužské pohlaví; peritoneální nádory; prospektivní studie; rektum; Peritoneal Neoplasms; následné studie; Prospective Studies